Laser written nitrogen vacancy centers in diamond integrated with transfer print GaN solid immersion lenses - Cheng, X; Wessling, NK; Ghosh, S; Kirkpatrick, AR; Kappers, MJ; Lekhai, YND; Morley, GW; Oliver, RA; Dawson, MD; Smith, JM; Salter, PS; Strain, MJ (Society of Photo-Optical Instrumentation Engineers, 2024)
Laser-written Nitrogen Vacancy (NV−) centers are combined with transfer-printed GaN micro-lenses to increase fluorescent light collection by reducing total internal reflection at the planar diamond interface. We find a 2x improvement of fluorescent light collection using a 0.95 NA air objective at room temperature, in agreement with FDTD simulations. The nature of the transfer print micro-lenses leads to better performance with lower Numerical Aperture (NA) collection, as confirmed by results with a 0.5NA air objective which show improvement greater than 5x. The approach is attractive for scalable integrated quantum technologies.